Knowledge, nobility and ethics in care as a human service - Cervera Vallejos, Mirtha Flor (2022)
In today's nursing, experience, updating, humanity and ethics are accompanied by a fruitful work with a promising future, like an unfading torch that illuminates the often dark and difficult path of the sick, convalescent or dying person. The nursing staff possesses a great deal of temperament, characteristic of those who have combined professional knowledge and ethical courage when providing care to people or groups vulnerable due to age, illness or those who need permanent guidance, such as families, adolescents and older adults, carriers of genetic or acquired comorbidities.